Is Asia a 'Post-Religional' Society? The Post-Religional Paradigm and its Others - Pilario, Daniel Franklin (Horizonte, 2015)
This article discusses the relevance and applicability of the 'post-religional paradigm' as proposed by EATWOT (Ecumenical Association of Third World Theologians) in the Asian contexts. It also inquires on how the Asian phenomenon and its interpretations relate to the crisis of religions in Western societies. It attempts to answer this problematic through four steps: a summary of the theological proposal and its relationship with the Western sociologies of religion; a search for a viable framework with which to understand religions in post-secular societies; discussion on the "discourses of Asia" and the corresponding view on religion; an elaboration of my preferred framework with some examples from the Asian situation. I argue that a viable theological proposal on post-religional paradigm should start from the analysis of how religious discourses and practices navigate with concrete socio-historical forces on the ground. Consequent to this view is the assertion that there is no universal sociology/theology of religion's development but multiple and complex religious discourses in specific contexts.